Consumer Behaviour and Social Entrepreneurship: The Case of South Korea - Lee, Chong Kyoon; Mousa, Fariss Terry; Lee, Jinyoung; Lee, Seung Hwan “Shawn” (Journal of Social Entrepreneurship, 2024)
Although social entrepreneurship has gained popularity and our understanding of social entrepreneurship has evolved, insufficient attention has been given to understand the behaviours of consumers, a key stakeholder of social entrepreneurship. Because consumers directly impact the performance of social enterprises, it is imperative to address this research gap. Relying on the theory of planned behaviour, we examine the relationship between consumers’ intentions and behaviours when purchasing social enterprise products and services. Moreover, this study explores how consumers’ sociodemographic characteristics, such as political ideology, trust towards social entrepreneurship, and household income, influence the relationship between consumers’ intentions and behaviours. Based on a sample of randomly selected 972 Korean consumers, this study finds a consumer’s intention is positively associated with behaviour, and the positive relationship between intention and action is strengthened when a consumer has a progressive political ideology and higher income level.
Keywords: consumer behaviour; Social enterprise; South Korean Context; stakeholders